Plasmodesmata distribution and sugar partitioning in nitrogen-fixing root nodules of Datisca glomerata - Schubert, Maria; Büttner, Michael (Planta, 2010)
To understand carbon partitioning in roots and nodules of Datisca glomerata, activities of sucrose-degrading enzymes and sugar transporter expression patterns were analyzed in both organs, and plasmodesmal connections between nodule cortical cells were examined by transmission electron microscopy. The results indicate that in nodules, the contribution of symplastic transport processes is increased in comparison to roots, specifically in infected cells which develop many secondary plasmodesmata. Invertase activities are dramatically reduced in nodules as compared to roots, indicating that here the main enzyme responsible for the cleavage of sucrose is sucrose synthase. A high-affinity, low-specificity monosaccharide transporter whose expression is induced in infected cells prior to the onset of bacterial nitrogen fixation, and which has an unusually low pH optimum and may be involved in turgor control or hexose retrieval during infection thread growth.